Long non-coding RNA 2310069B03Rik functions as a suppressor of Ucp1 expression under prolonged cold exposure in murine beige adipocytes. Issue 2 (1st February 2020) - Iwase, Mari; Sakai, Shoko; Seno, Shigeto; Yeh, Yu-Sheng; Kuo, Tony; Takahashi, Haruya; Nomura, Wataru; Jheng, Huei-Fen; Horton, Paul; Osato, Naoki; Matsuda, Hideo; Inoue, Kazuo; et al.
ABSTRACT: Specific conditions, such as exposure to cold, can induce the production of brown-like adipocytes in white adipose tissue. These adipocytes express high levels of uncoupling protein 1 (UCP1) and energy expended by generating heat. Thus, these are a potential target for the prevention or treatment of obesity. The present study involved a comprehensive analysis of the adipose tissue to understand the relationship between long non-coding RNA (lncRNA) 2310069B03Rik and UCP1. Cold exposure increased both lncRNA 2310069B03Rik and Ucp1 expression in inguinal white adipose tissue (iWAT). However, overexpression of lncRNA 2310069B03Rik suppressed the Ucp1 mRNA expression and the promoter activity of UCP1 in the iWAT primary adipocytes. In addition, compared to the early induction of Ucp1 expression by cold stimulation, the induction of lncRNA 2310069B03Rik expression was later. These results suggest that lncRNA 2310069B03Rik functions as a suppression factor of Ucp1 expression. Graphical abstract: : Long non-coding RNA 2310069B03Rik functions as a suppression factor of Ucp1 expression.